USE OF CBCT – C0NE BEAM COMPUTED TOMOGRAPHY WITHIN DIAGNOSIS OF HYPERDONTIA – A CASE STUDY - Josifov, Danijel (Journal of Morphological Sciences, 2020)
Awareness of hyperdontia pattern/prevalence can be useful in early diagnosis and prevention by general practitioners, pediatric dentists, and orthodontists. Since the previous results regarding the pattern of hyperdontia (supernumerary teeth) are controversial, this study aimed to assess this issue in an 8-year-old boy.Cone Beam Computed Tomography (CBMT) is a relatively new three-dimensional imaging technology, which has been specifically developed for imaging of the teeth and jaws. The main aim of this paper is to acquaint the dental team with various forms of this technology and its potential applications. An understanding of the underlying principles will allow the users of this technology to tailor the imaging protocol to the patient's individual needs to achieve appropriate imaging at the lowest radiation dose. The second (narrow) aim of the paper is  an overview of the fundamental principles of operation of maxillofacial CBCT technology; and discussing the role of CBCT in the precise positioning of supernumerary teeth and choosing the most appropriate method for their removal. CBCT is a result of dramatic advances in computer and electronic technology and (along with similar advances in scanning and manufacturing) is one of the key components in the rapidly evolving field of digital dentistry. It is becoming widely available and has applications in implant dentistry, endodontics and oral surgery. K eywords: hyperdontia, supernumerary teeth, orthodontic patients, prevalence